2009
DOI: 10.1186/1471-2407-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the steroid and xenobiotic receptor, SXR, induces apoptosis in breast cancer cells

Abstract: BackgroundThe steroid and xenobiotic receptor, SXR, is an orphan nuclear receptor that regulates metabolism of diverse dietary, endobiotic, and xenobiotic compounds. SXR is expressed at high levels in the liver and intestine, and at lower levels in breast and other tissues where its function was unknown. Since many breast cancer preventive and therapeutic compounds are SXR activators, we hypothesized that some beneficial effects of these compounds are mediated through SXR.MethodsTo test this hypothesis, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 72 publications
0
69
1
2
Order By: Relevance
“…However our observations are in stark contrast to recent observations that PXR induces apoptosis in colon (60) and breast cancer (18) and predicts for significantly improved survival in esophageal cancer (61). The discrepancy is likely due to methodological differences.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However our observations are in stark contrast to recent observations that PXR induces apoptosis in colon (60) and breast cancer (18) and predicts for significantly improved survival in esophageal cancer (61). The discrepancy is likely due to methodological differences.…”
Section: Discussioncontrasting
confidence: 56%
“…This promiscuous xenosensor plays a central role in regulating liver and gastrointestinal drug metabolism. However, PXR is widely expressed in many different tissues and tumors (e.g., colon, breast, and ovary) (15)(16)(17)(18)(19). In search of tissue-specific functions of PXR, we previously demonstrated that PXR activation induces ovarian cancer cell proliferation and drug resistance (20).…”
Section: Introductionmentioning
confidence: 99%
“…Wan and colleagues reported the mouse lacking PXR showed decreased liver regeneration after partial hepatectomy and the PXR-regulated lipid homoeostasis, which fuels the liver regeneration, may have a role in the suppressed liver growth (Dai et al, 2008). Verma et al (2009) reported that PXR activation induced apoptosis in breast cancer cell line and PXR is anti-proliferative and the effect is mechanistically dependant on the local production of NO and NO-dependent upregulation of p53. As the HT29 cells have mutated p53, the mechanism of PXR-regulated inhibitory effects on HT29 growth may differ from the NO-dependent upregulation of p53 reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnane glycosides are structurally similar to cardiac glycosides such as digoxin (Deepak et al 1997), which inhibit calcium exchangers, thereby leading to a prolonged increase in intracellular calcium concentration and stimulation of caspases and apoptosis. Another possible mechanism of action is the activation of the steroid and xenobiotic receptor (SXR), an orphan steroid receptor, which induces apoptosis in breast cancer cells (Verma et al 2009). Further studies are required, but the activation of the SXR is an exciting possibility.…”
Section: Mcf-7 Cellsmentioning
confidence: 99%